Spatial Distribution of Genetic, Ploidy, and Morphological Variation of the Edaphic Steno-Endemic Alyssum moellendorfianum (Brassicaceae) from the Western Balkans - Jasna Hanjalić Kurtović; Belma Kalamujić Stroil; Sonja Siljak-Yakovlev; Naris Pojskić; Adaleta Durmić-Pašić; Alma Hajrudinović-Bogunić; Lejla Lasić; Lejla Ušanović; Faruk Bogunić (Plants)
Polyploidy is a powerful mechanism driving genetic, physiological, and phenotypic changes among cytotypes of the same species across both large and small geographic scales. These changes can significantly shape population structure and increase the evolutionary and adaptation potential of cytotypes. Alyssum moellendorfianum, an edaphic steno-endemic species with a narrow distribution in the Balkan Peninsula, serves as an intriguing case study. We conducted a comprehensive analysis of genetic diversity and population structure across the species’ range, employing an array of genetic techniques (nuclear microsatellites, amplified fragment length polymorphisms, and plastid DNA sequences), flow cytometry (FCM), morphometry, and pollen analysis. The study reveals two genetic lineages: spatially distributed diploid and tetraploid cytotypes. Clear divergence between diploids and tetraploids was shown by AFLP, while plastid DNA sequences confirmed private haplotypes in each of the studied populations. Higher genetic diversity and allelic richness following the north-south pattern were documented in tetraploids compared to diploids, as indicated by nuclear microsatellites. Morphometric analysis via principal component analysis (PCA) and canonical discriminant analysis (CDA) did not reveal any divergence between diploid and tetraploid cytotypes. Nonetheless, a distinction in pollen size was clearly observed. The results suggest an autopolyploid origin of tetraploids from diploid ancestors. Despite the population fragmentation in a very small geographic range, these populations harbour high genetic diversity, which would allow them to remain stable if natural processes remain undisturbed.